The Islamic Principles of Social Justice: Maulana Abul Kalam Azad and Nonviolent Civil Disobedience. (March 2015) - Alvi, Hayat
The idea of nonviolent civil disobedience is to act against injustice and unjust laws. This has been Mahatma Gandhi's motivation, as well as Maulana Abul Kalam Azad's. For an Islamic religious authority of Maulana Azad's stature and caliber to embrace nonviolent activism for the sake of social justice, it is a significant change in the course of action in Islam against oppression. The concepts of justice/injustice, oppression, and social justice need to be examined in historical context, beginning with early Islamic history, followed by the period of British colonial rule and the Indian struggle against it as led by Mahatma Gandhi and Maulana Azad. This article analyzes the principles of Maulana Azad in the struggle against injustice, and how that compares to the principles and practices of Islamic militancy and jihadism. The latter are viewed as illegitimate, while Maulana Azad's Islamic credentials render his acceptance of nonviolent civil disobedience as far more legitimate.